Sistem pengendali saklar berbasis Nodemcu ESP8266 dengan aplikasi MQTT dan Google Assistant - Bekti Maryuni Susanto; Agus Hariyanto; Denny Wijanarko; Moch Khafil Albab (Institut Teknologi Dirgantara Adisutjipto, 2022)
The Internet of Things (IoT) provides the ability to connect many things or devices over the internet. Message Queue Telemetry Transport (MQTT) is a Client Server published/subscribed message transport protocol. The protocol runs on top of TCP/IP, or on top of other network protocols that provide sequential, lossless bi-directional connections. The system developed in this study consists of three layers based on the perception layer, network layer and application layer. The perception layer consists of relays that are used to control the screen based on user input. The network layer consists of the MQTT server and Google assistant connected to the IFTTT service. This system was developed with the aim of making it easier for humans to monitor home electrical devices remotely. The test results show that this system can be used to control the switch quickly even though it really depends on the quality of the internet network.